Media Promotional for Art in Tangerang City with Audio Visual Adobe Creative - Shino, Yamato; Kenta, Hiroshi; Mertayasa, I Komang (Aptisi Transactions On Technopreneurship (ATT), 2022)
Historical buildings contain elements of art in the city of Tangerang, which have good potential to become a tourist destination, but they must be appropriately managed to generate a source of income for the region. The diversity of ethnicities, races, and religions is an important supporting factor in influencing the diversity of artistic values. One of them is the Lenggang Cisadane Dance which is typical art of Tangerang City. And many historical buildings such as the Thousand Doors Mosque, Fortress Museum, Kalipasir Mosque, Al-Adzhom Mosque, etc. Every historical asset needs to be introduced to the public, and this is the authority of the Communication and Information Technology Office (DisKomInfo). However, the information media used is still very minimal. Therefore, a study was conducted using the KPM method, which outputs video using the Adobe Creative Suite. The media needed to maximize promotion and information is the Video Art, Tourism, and Historic Buildings, with an informative and practical display. The beauty of Tangerang City holds history and high artistic value, so it is hoped that this research can increase public interest in studying history and doing tourism.